Methods and algorithms of intellectual support in making managerial decisions in the implementation of security alarm tasks at objects of special importance - O. V. Tolstykh; O. V. Isaev (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. Currently, there is a problem of developing low-cost and functional SOTC controllers with support for algorithms for controlling the totality of elements of life support systems and subsystems of HMB OOV, for example, access control and management systems (ACS), as well as the possibility of integrating the proposed SOTC solutions into existing HMB facilities. This article proposes circuit engineering and software approaches to the organization of promising STS implemented on the basis of programmable microcontrollers. Method. To achieve this goal, a systematic approach has been applied, and obtaining a quantitative assessment of the probabilistic characteristics of detecting an intruder is based on the use of mathematical modeling methods. Result. A completed circuit design for a special-purpose COTS controller has been developed, capable of solving highly specialized tasks in OOV, and also characterized by an obvious balance of functional characteristics and cost indicators. Conclusion. The developed SOTS based on universal microcontrollers makes it possible to ensure ease of implementation of security complexes and, if necessary, change the composition of the modules used to transform the intended purpose of the OTS device while maintaining the parametric indicators of the quality of the information system, helps to optimize control and automation processes at OOV in conditions of minimizing costs.